CIRURGIA RECONSTRUTIVA DA PIRÂMIDE NASAL - Machado de Sousa, Pedro; Alexandre, Carlos; Marques, Canas; Marta Pimentel, João (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.